2018
DOI: 10.1111/jocn.13964
|View full text |Cite
|
Sign up to set email alerts
|

The universal, collaborative and dynamic model of specialist and advanced nursing and midwifery practice: A way forward?

Abstract: The model design has Universal application in a range of contexts "U." It is Collaborative in its inclusivity of all key stakeholders "C." The model is Dynamic pertinent to accommodating movement of nurses and midwives across health continua rather than plateauing in very specialised "silos" "D."

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 33 publications
0
18
0
1
Order By: Relevance
“…There is a growing interest in the implementation of the role of ANPs (Casey, O’Connor, Cashin, et al, ; Casey, O’Connor, Nicholson, et al, ; Chavez et al, ; O'Connor et al, ; Woo, Lee, & Tam, ). There is a growing interest in the development and implementation of the role of ANPs and AMPs (Chavez, Dwyer, & Ramelet, ; O'Connor et al, ; Woo et al, ). Franks and Howarth () found that similar roles were enabled by the high public priority, legislative, policy support and support from organisational leaders and managers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is a growing interest in the implementation of the role of ANPs (Casey, O’Connor, Cashin, et al, ; Casey, O’Connor, Nicholson, et al, ; Chavez et al, ; O'Connor et al, ; Woo, Lee, & Tam, ). There is a growing interest in the development and implementation of the role of ANPs and AMPs (Chavez, Dwyer, & Ramelet, ; O'Connor et al, ; Woo et al, ). Franks and Howarth () found that similar roles were enabled by the high public priority, legislative, policy support and support from organisational leaders and managers.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, although “factual evidence supporting the positive impact of these roles is urgently needed” (Casey, O’Connor, Nicholson, et al, , p. 3014), it is imperative that the factors enabling and hindering the development and implementation of advanced nursing and midwifery practice roles are identified to support future planning and the subsequent measurement of the impact of these roles. A future model to guide the development of specialist and advanced roles has been reported elsewhere (O' Connor et al, ). This paper explores the enablers and challenges to the development and implementation of advanced practice roles in the Irish health care system and discusses strategies to enhance the enablers and overcome the challenges.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, at the end of the incomer phase, recognition by nursing specialties of the transition as part of the experiential learning that enhances continuing lifelong learning of the specialist nurse was a key attribute for specialty nurses. A previous ‘universal, collaborative and dynamic model’ of specialist and advanced nursing and midwifery practice supports that lifelong learning embraces capability in experiential learning as a concept that ensures continued lifelong learning 72. Benner’s novice to expert model is also grounded on the importance of experiential learning which our work is placed and extends 17.…”
Section: Discussionmentioning
confidence: 83%
“…The utility of specialist or generic fields of nursing has been being debated (ANMF 2019; Zahran et al 2012) amid concerns that specializations in nursing may lead to practice "silos" and limit transferability (O'Connor et al 2018). Conversely, a specialist nurse (e.g., postgraduate/masters level) with advanced knowledge, cognitive and research skills may have increased capacity to transfer these skills/qualities to nonspecialist or generalist integrated practice areas (O'Connor et al 2018;Zahran et al 2012).…”
Section: Evolution Of Higher Education In Nursingmentioning
confidence: 99%